Optimal Tax/Expenditure Competition Strategy of Governments in the Presence of Time Inconsistency : The Case for Investment Tax Abacemencs. (IMF Working Papers; Working Paper, 1990)
Businesses which seek the location that offers the highest profitability are likely to consider tax incentives and the level of government services available. However, once a business commits itself to a locality, high moving costs render it vulnerable to future tax increases or denial of government services. Fear of time inconsistency will lower expected business profitability in a region. This paper indicates that a developing country or locality can attract a higher level of capital with a tax abatement scheme which provides a subsidy (funded by a capital income tax) equivalent to moving/setup costs.